Unlinkable and Revocable Secret Handshake. (14th January 2021) - Tian, Yangguang; Li, Yingjiu; Mu, Yi; Yang, Guomin
Abstract: In this paper, we introduce a new construction for unlinkable secret handshake that allows a group of users to perform handshakes anonymously. We define formal security models for the proposed construction and prove that it can achieve session key security, anonymity and affiliation hiding. In particular, the proposed construction ensures that (i) anonymity against protocol participants (including group authority) is achieved since a hierarchical identity-based signature is used in generating group user's pseudonym-credential pairs and (ii) revocation is achieved using a secret sharing-based revocation mechanism.